Quality of malting barley grown under differentcultivation - Petr, J.; Škeřík, J. (BrewingScience, 2000)
Three year trials were conducted to investigate the set of spring barley varieties cultivated according to principles of ecological agriculture or using the ordinary agrotechnics (fertilization, seed treatment, herbicides, fungicides, insecticides). The weather conditions affected most of the quality traits more than e.g. nitrogen fertilization or system of cultivation. Significant differences among years were recorded in protein content in grain, relative extract at 45 °C, Kolbach index, diastatic power, and apparent final attenuation. The cultivation system substantially influenced the β-glucan content in wort, it was surprisingly low under ecological system of cultivation. The effect of the cultivation system was also proved in the hot water extract and partially in Kolbach index and friability.